PHARMACEUTICAL AND CLINICAL CHALLENGES OF BIOLOGICAL MEDICINES: ONGOING HURDLES FROM DRUG DEVELOPMENT TO THERAPEUTIC APPLICATIONS - SAYON PAUL; AVIK SARKAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Beyond conventional small drug molecules mostly of synthetic origin, clinical benefits have been well established by administering large complex biomolecules against different diseases including cancer, metabolic disorders, and infectious diseases. From insulin, its different derivatives and dosage forms to cutting-edge messenger ribonucleic acid (mRNA) based vaccines, stem cells, immunotherapy with chimeric antigen receptor T cells for cancer likewise offered novel, pivotal pathways in healthcare and helped in alleviating the corresponding diseases, maintaining the overall quality of life of patients. However, the lifecycle management of these biopharmaceuticals offers stern challenges, namely, the structural complexity of biomedicines impacting drug discovery and formulation development, multifaceted manufacturing processes involving living systems (e.g., mammalian cell lines, microbial agents, plants, fungi, etc.), temperature and humidity sensitive supply chain management, stringent regulatory requirements, invasive drug delivery approaches, monitoring immunogenicity after drug administration, etc. Animal and clinical testing of the biologics are also very challenging. Novel biopharmaceuticals including cell-based medicines, recombinant products, gene therapy products, etc. often face ethical and higher cost-related issues. Proper alignment of regulatory guidelines, innovative bioinformatics, and software-based drug discovery tools, implementation of quality by design approaches to identify critical quality parameters at the drug developmental phase, the suitable training to health-care professionals on usage, safety, immunogenicity, handling and storage of biopharmaceuticals would bestow clinical benefits of biopharmaceuticals to the desired patients. Continual research is going on to market new biopharmaceuticals in a cost-effective manner for difficult-to-treat terminal diseases preferably through peroral administration.